PREPARATION AND CHARACTERIZATION OF ANCHOVY (STOLEPHORUS SP) PROTEIN CONCENTRATE NANOPARTICLE USING IONIC GELATION METHOD - SAPIUN, ZULFIAYU; IMRAN, ARLAN K.; WICITA, PRISCA SAFRIANI; KAMBA, VYANI; SLAMET, NANGSIH SULASTRI (International Journal of Applied Pharmaceutics, 2020)
Objective: Nanoparticle preparation can increase the bioavailability of anchovy protein. This study aims to optimize and characterize anchovy protein concentrate nanoparticle based on volume comparison of chitosan-TPP (Tripolyphosphate) matrix in forming the size of anchovy protein concentrate nanoparticle with ionic gelation method. Methods: Fresh anchovy was extracted by an acid-base method using solvents of NaOH and HCl to get protein concentrate. After that, it was conducted by formulating anchovy protein concentrate into a mixture of chitosan-TPP matrix with volume ratio which was divided into 5 series of variations, namely F1 without matrix, F2 1:1, F3 1:3, F4 1:5 and F5 1:7 ratio of chitosan to TPP, then formed matrix was determined the value of the encapsulation efficiency and characterized using a particle size analysis tool. Results: The results showed that the optimum volume comparison of the chitosan-TPP matrix in forming nanoparticle of anchovy protein concentrate was ratio 1:7 because this has a matrix encapsulation efficiency value of 99.11%, a small particle concentrate size of 687.26 nm, a good polydispersity index value of 0.406 and a value of zeta potential of+12.9 mV. Conclusion: The optimum formula of the chitosan-TPP matrix volume ratio in forming anchovy protein concentrate nanoparticle is F5 with the ratio of chitosan-TPP matrix mixture 1:7.